1995
DOI: 10.1007/bf00187627
|View full text |Cite
|
Sign up to set email alerts
|

The significance of major pheromone components and interspecific signals as expressed by receptor neurons in the oriental tobacco budworm moth, Helicoverpa assulta

Abstract: Receptor neuron specificities for intra-and interspecific chemical signals were determined in males of Helicoverpa assulta, by testing single neurons for twelve heliothine produced compounds and two chemical analogues. Three types of receptor neurons were identified in the male specific sensilla trichodea type 1. 1. One large group of neurons (29 out of 63) was tuned to the major pheromone component (Z)-9-hexadecenal, in contrast to results obtained previously in a related species, where the information from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
1
24
1
Order By: Relevance
“…2C). The identification of the neuron types was confirmed by the concordance between the data presented here and those previously reported by Berg and Mustaparta (1995). The large-amplitude Z9-16:AL neurons responded, in addition to the key compound, weakly to the highest concentration of Z9-14:AL (n ϭ 142) ( Fig.…”
Section: Sensilla Containing Two Colocalized Receptorsupporting
confidence: 91%
See 1 more Smart Citation
“…2C). The identification of the neuron types was confirmed by the concordance between the data presented here and those previously reported by Berg and Mustaparta (1995). The large-amplitude Z9-16:AL neurons responded, in addition to the key compound, weakly to the highest concentration of Z9-14:AL (n ϭ 142) ( Fig.…”
Section: Sensilla Containing Two Colocalized Receptorsupporting
confidence: 91%
“…The second, infrequently occurring sensillum type of H. assulta, the A-type, housing the receptor neurons detecting Z11-16:AL also corresponds with a similar, but abundant type in other heliothine moths, including H. zea, H. armigera, H. virescens, and H. subflexa (Almaas and Mustaparta, 1990;Hansson et al, 1995;Berg et al, 1995;Mustaparta, 1997Mustaparta, , 1998Cossé et al, 1998;Skiri, 1999;Baker et al, 2004). The occasional appearance of a nonresponding, small-amplitude neuron, as shown in Figure 4, is in accordance with the data from H. virescens (Berg et al, 1998).…”
Section: Compartmentalization Of the Antennal Receptor Neuronsmentioning
confidence: 94%
“…For example, males of H. vires c ens possess two types of pheromone sensory neurons tuned to cis -11-hexadecenal (Z11-16:AL) and cis -9-tetrdecenal (Z9-14:AL), respectively, whereas two additional neuron populations are tuned to substances produced by females of sympatric species, one to cis -11-hexadecenyl acetate (Z11-16:AC) and the other to cis -11- hexadecenol (Z11-16:OH; Almaas et al, 1991; Berg et al, 1995, 1998; Hansson et al, 1995). In males of the Oriental tobacco moth, H. assulta , two types of pheromone sensory neurons are tuned to cis -9-hexadecenal (Z9-16:AL) and Z11-16:AL, respectively, whereas a population of Z9-14:AL-responding neurons carries interspecific information (Berg and Mustaparta, 1995; Berg et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…The interrupting effect of this compound was also seen at a relatively low amount, 2%, when it was added to a 1:20 blend of Zll-16:AL and Z9-16:AL (Cork et al 1992). It is, therefore, interesting that out of all the heliothine pheromone components tested, the receptor neurons tuned to Z9-14:AL in H. assulta also responded to Z9-16:OH (Berg and Mustaparta, 1995). It seems, therefore, that the Z9-14:AL neurons could mediate information from more than one interspecific signal that can interrupt pheromone mediated attraction.…”
Section: Discussionmentioning
confidence: 98%
“…Electrophysiological studies of receptor neuron specificities for compounds identified in the female pheromone glands of heliothine moths were conducted on male H. assulta from Korea (Berg and Mustaparta 1995). In that study, recordings from sensilla trichodea type I revealed three types of receptor neurons, each type was found to be tuned to one compound.…”
Section: Introductionmentioning
confidence: 99%